COGNITIVE DIFFICULTIES AMONG ASIAN AMERICAN OLDER ADULTS: RESULTS FROM THE AMERICAN COMMUNITY SURVEY. (20th December 2022) - Nguyen, Duy; Liu, Rui; Lee, Yookyong
Abstract: While Asians are the fastest growing racial group in the United States, limited research exists on their health needs, especially among older adults. Cognitive difficulties increase disease and caregiving burdens, but little is known about patterns of cognitive health among Asian American older adults. This study fills the knowledge gap by using data from the 2015-2019 American Community Surveys to examine the relationship between Asian ethnicity and gender on cognitive health. This analysis focuses on respondents aged 65 and over from the six most populous Asian American groups: Chinese, Filipino, Indian, Japanese, Korean, and Vietnamese (n=100, 538). Weighted, adjusted logistic regression analyses tested for the effects of Asian ethnicity and gender on cognitive difficulties. Multivariate analyses showed Filipino, Indian, and Vietnamese older adults were more likely than Chinese to report cognitive difficulties. Additionally, Asian American women were more likely to report cognitive difficulties compared to Asian American men. Joint effect analyses were statistically significant, thus we examined separate regression analyses by Asian ethnicity. Results showed that Vietnamese women were more likely than Vietnamese men to report cognitive difficulties. Across Asian ethnic groups, family relationships and economic factors play a major role in having a cognitive difficulty. Overall, the results suggest that ethnic-specific analysis of the Asian American reveals a fuller picture of health in older adulthood. Future research needs to dive more deeply into the sociocultural and economic dimensions of health. Further, culturally appropriate policy and practices are needed to promote successful aging among older Asian Americans.